Diversity of bivalve and gastropod in the coastal waters of Kundur Island Karimun Regency Kepulauan Riau Province - Adeka Febriyanti; Efawani '; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Coastal waters of Kundur Island is inhabit by marine organisms, including bivalve and gastropod. A research aims to determine the diversity of bivalve and gastropod in the coastal waters of the Kundur Island was conducted on Desember 2015-January 2016. Samples were taken at eight stations. Bivalve and gastropod indentification was based on Dharma (1992), Roberts et al. (1982), Morris (1966) and Abbott (1991). There were 10 species of bivalves and 28 species of gastropods present. The is highest bivalves and gastropods density were in the station 3, there was 6 organisms / m2 and the lowest was in the station 1 which was 3 organisms/ m2. Nerita funiculata shown the highest relative density (57%) while Ostrea lurida was the lowest (0.3%). The diversity index (H’) ranged from 1.28-2.81 (average), the evenness index (E) was 0.60-0.82. The dominant index (C) was 0.25-0.54, and it means that there was not dominant species. Based on data obtained, it can be concluded that the coastal waters of the Kundur Island is categorized as good.Keywords: Diversity, bivalve, gastropod, Kundur Island